School Branding Strategies to Increase the Appeal to Prospective Students at SDIT Insan Madani Madiun - Fatha Ardli Kusuma; Syamsul Arifin; Azid Syukroni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
School branding strategies are a key factor in the competitive landscape of educational institutions, particularly in attracting prospective students. This study aims to examine the school branding strategies implemented by the Insan Madani Integrated Islamic Elementary School in Madiun to attract prospective students, identify the impact of these strategies, and determine the supporting factors and challenges in their implementation. This study employs a qualitative method using a case study approach. Data were collected through observation, interviews, and documentation involving various stakeholders, such as the foundation chairperson, the school principal, the student recruitment team, teachers, and parents. Research findings indicate that Insan Madani Integrated Islamic Elementary School in Madiun implements a school branding strategy through character development, academic achievement, tahsin and tahfizh programs, extracurricular activities, and the use of digital branding. The implementation of school branding has had an impact on several aspects, such as increased trust and loyalty among parents toward the school, an increase in student enrollment, the establishment of a positive image in the public’s mind, and enhanced institutional competitiveness. This serves as proof that the Insan Madani Integrated Islamic Elementary School in Madiun has successfully established itself as a top choice and the first choice for parents. Factors supporting the institution’s branding include educators or teachers, an Islamic-themed environment, the involvement of parents or guardians, and adequate facilities and infrastructure. However, the obstacles or challenges faced include the emergence of educational institutions with nearly identical branding and the need to meet the increasingly diverse needs of students. This study is expected to enrich the discussion on the management of effective school branding strategies so that schools can excel and remain relevant within the community.